Mixing‐Induced Orientational Ordering in Liquid‐Crystalline Organic Semiconductors - Kiyoshi Nikaido; Satoru Inoue; Reiji Kumai; Toshiki Higashino; Satoshi Matsuoka; Shunto Arai; Tatsuo Hasegawa (Advanced Materials Interfaces, 2022)
Abstract Organic semiconductors (OSCs) often exhibit thermotropic liquid‐crystalline (LC) phases in which molecular orientational order is partially lost. The formation of a temporary LC state via a solution process is expected to promote printing‐based device production, although a method of controlling molecular ordering over LC states has not yet been developed. Here, it is demonstrated that long‐axis molecular ordering can be controlled under ambient conditions using unsymmetrically alkylated OSCs with high layered crystallinity. Introducing a small amount of OSC molecules with longer alkyl‐chain lengths leads to the conversion of the long‐axis disordered phase into a bilayer‐type ordered phase with improved hole mobility in the transistor characteristics. Analyses of the entropies of the transitions to the smectic LC phases at elevated temperatures demonstrate that the long‐axis molecular ordering can be driven by a balance between intralayer flip–flop motion and core–core interactions through LC phases. The proposed LC‐mediated solution processing paves the way toward high‐end printed electronics.